PENERAPAN FORESEEABILITY OF HARM DAN PRECAUTIONARY PRINCIPLE DALAM PENGATURAN SAMPAH PLASTIK SEBAGAI LAND-BASED SOURCE - Adori Raka Susanto (BELLI AC PACIS (Jurnal Hukum Internasional), 2022)
Marine pollution caused by plastic waste is regarded as a land-based sources type of marine pollution. The current regulation of land-based sources pollution, especially plastic waste is still too general and not effective. This legal research aims to analyze the existing international regulations regarding land-based pollution and how to implement the foreseeability of harm and precautionary approach principles for specific international arrangements regarding plastic waste pollution in the future. This article concludes that the application of the principle is important to ensure the effectiveness of the regulation regarding plastic waste, since the nature of the principle is to prevent.